Implementasi Pencegahan Infeksi Silang di Klinik Gigi melalui Program Pengabdian kepada Masyarakat - Fidzah Nurfajrina Murad; Zahrawi Astrie Ahkam; Amirah Maritsa; Hasrini Hasrini; Dwi Rezky Aulyah (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Cross-infection prevention is a crucial aspect of health services, especially in dental clinics that often face high risks of infection transmission. This community service program aims to improve the knowledge and skills of health workers and the community in preventing cross-infection in dental clinics. These activities include counseling, practical training, and evaluation in several dental clinics, with a focus on the implementation of hygiene protocols, the use of personal protective equipment (PPE), and sterilization of medical devices. The results of this program showed a significant increase in the understanding and implementation of cross-infection prevention procedures, as measured by questionnaires before and after the program implementation.